Synthesis, crystal structure and spin exchange coupling in polynuclear carboxylates with Li2(VO)2 metal core. (24th November 2017) - Bazhina, Evgeniya S.; Aleksandrov, Grigory G.; Kiskin, Mikhail A.; Efimov, Nikolay N.; Ugolkova, Elena A.; Korlyukov, Alexander A.; Nikitin, Oleg M.; Magdesieva, Tatiana V.; Minin, Vadim V.; Sidorov, Alexey A.; Miller, Joel S.; Eremenko, Igor L.
Graphical abstract: Li atoms in [Li2 (VO)2 ( μ -OOCR)6 (bpy)2 ] (R = CMe3 (2 ), CF3 (3 )) contribute to the weakening of spin coupling between two vanadium(IV) centers in comparison with [(VO)2 ( μ -OH)( μ -OOCCMe3 )2 (bpy)2 ] (1 ). Different types of weak antiferromagnetic spin–spin interactions are detected in similarly constructed molecules2 and3 : in2 – intramolecular, but in3 – probably intermolecular exchange. Abstract: Crystals of binuclear complex [(VO)2 ( µ -OH)( µ -Piv)2 (bpy)2 ](OTf) (1 ) have been obtained by the reaction of [VO(H2 O)5 ](OTf)2 (OTf = CF3 SO3 −, Piv = (CH3 )3 CCO2 − ) with 2, 2′-bipyridine (bpy) and lithium trimethylacetate (pivalate), Li(Piv), in a ratio of 1:1:2 in MeCN. Change of the reagent ratio to 1:1:3 resulted in the bimetallic compound [Li2 (VO)2 ( µ -Piv)6 (bpy)2 ] (2 ), which was isolated in the form of2 ·MeCN and2 ·CH2 Cl2 solvates. Replacement of Li(Piv) with lithium trifluoroacetate Li(Tfac) (Tfac = CF3 CO2 − ) results in the bimetallic compound [Li2 (VO)2 ( µ -Tfac)6 (bpy)2 ] (3 ). A similar reaction with lithium trichloroacetate, Li(Tcac) (Tcac = CCl3 CO2 − ), in ethanol gives the mononuclear complex [VO(Tcac)(bpy)2 ](OTf) (4 ). The structures of1 –4 were determined by single crystal X-ray diffraction. The magnetic properties (2–300 K) and EPR spectra of compounds1 –3 have been studied. Using the ESEEM (electron spin echo envelope modulation) method it has been shown that the mononuclear cation [VO(Tcac)(bpy)2 ] + of complex4 has partial spin density transfer from the V IV atom to donor ligands (in particular, the bpy nitrogen atoms). According to EPR spectroscopy data and quantum-chemical calculations, a similar spin density distribution is observed for2 and3, though spin exchange in these compounds is hindered by lithium ions, which contain no spin density and block electron density delocalization in the bridging system between the "magnetic" vanadium ions. Electrochemical properties of compounds2 and3 confirm the vanadium(IV) oxidation state.